Effect of NaBr on the Structural, Thermal and Mechanical Properties of HPMC:NaBr Composite Films - Kumar, Sunil; Raghu, S.; Demappa, T.; Sannappa, J. (Asian Journal of Chemistry, 2022)
The hydroxypropyl methylcellulose (HPMC):sodium bromide (NaBr) composite films were prepared using different concentrations by solution casting method. The crystalline percentage of the pure HPMC was reduced from 74% to 60% upon the incorporation of 0.7 wt.% of NaBr salt, which suggests that the NaBr salt disrupted the host polymer crystalline phase. The two-phase microstructure in the morphological images reflects the phase separation at different concentrations of dopant. The functional studies revealed the considerable variation of intensity and the shift of peaks due to the action of NaBr in the host polymer matrix. The HPMC showed a large increase in the glass transition temperature (Tg) from 65 ºC to 86 ºC and simultaneously reduction in the weight percent loss was observed. The mechanical analysis revealed that the added dopant has a significant effect on the mechanical properties of HPMC.